Intellectual system for rendering transportation services - Perkhun Bohdan (онлайн, 2020)
The information system "Rendering of motor transport services" is considered. The general description of the system and its relevance is made. Examples of known similar systems are given. Their advantages and disadvantages for consideration in the information system development are analyzed. A detailed description of each of the components of the information system is made, namely: server part, program for ordering services and database. A stepby-step description of the process of creating each of these modules of the system is made. The choice of programming language, web tools, startup devices, operating system, database management system is justified. The principle of information system operation is described, the conceptual model of the system is demonstrated. The example of using this information system in real conditions is given. Instructions for typical use of the information system by the user are provided. The results are analyzed and conclusions are drawn regarding the relevance of the information system creation and its practical application.
Keywords: information systems, driver search, system analysis, database man agement system, conceptual model, functional model